How relevant is Integrated Reporting? - Lopes, A.I.; Oliveira, J.; Coelho, A.M.C. (41th Annual Congress of European Accounting Association, 2018)
The present study is focused on the potential market benefits of presenting a high quality Integrated Report. Specifically, this preliminary research assess whether such characteristic is value relevant to investors. We investigate whether the market valuation of traditional accounting measures (book value of equity and net income) is higher for companies presenting an integrated report considered as "leading practice” when compared to companies publishing a regular integrated report. Our sample includes all the unique companies from the IIRC Examples Database. Financial and non-financial data were collected for a period of 10 years starting in 2006. Main findings confirm that either the book value of equity or operating income have a positive and statistically significant impact on the market value and, as expected, those relationships are intensified when they come from companies recognized as “best practice” in the integrated reporting process.